2014
DOI: 10.4141/cjss-2013-093
|View full text |Cite
|
Sign up to set email alerts
|

Long-term tillage and crop rotation effects on soil quality, organic carbon, and total nitrogen

Abstract: Long-term studies allow for quantification of the effects of crop production practices, such as tillage and crop rotation, on soil quality and soil C and N stores. In two experiments at Ridgetown, ON, we evaluated the long-term (11 and 15 yr) effect of tillage system and crop rotation on soil quality via the Cornell Soil Health Assessment (CSHA) at 0Á15 cm and soil organic C (SOC) and total N at 5-, 10-, and 20-cm increments to 120 cm depth. The CSHA soil quality score and SOC and total N were higher with no-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 26 publications
1
42
0
Order By: Relevance
“…Campbell et al (1993) found aggregate stability was influenced by long-term (30 years) management; long-term CT probably disturbed soil aggregates, facilitating a more rapid breakdown of crop residues than NT, thereby reducing aggregate stability. Likewise, previous long-term (9-12 years) research found higher aggregate stability in NT or minimal till plots than chisel or plow treatments in monoC or rotational C cropping in WI, USA (Karlen et al, 1994) at Elora, ON (Raimbault and Vyn, 1991) and Ridgetown, ON (Van Eerd et al, 2014). The higher aggregate stability in NT vs. CT may be in part a reflection of earthworm activity as influenced by tillage.…”
Section: Tillage Systemmentioning
confidence: 87%
See 4 more Smart Citations
“…Campbell et al (1993) found aggregate stability was influenced by long-term (30 years) management; long-term CT probably disturbed soil aggregates, facilitating a more rapid breakdown of crop residues than NT, thereby reducing aggregate stability. Likewise, previous long-term (9-12 years) research found higher aggregate stability in NT or minimal till plots than chisel or plow treatments in monoC or rotational C cropping in WI, USA (Karlen et al, 1994) at Elora, ON (Raimbault and Vyn, 1991) and Ridgetown, ON (Van Eerd et al, 2014). The higher aggregate stability in NT vs. CT may be in part a reflection of earthworm activity as influenced by tillage.…”
Section: Tillage Systemmentioning
confidence: 87%
“…The higher aggregate stability in NT vs. CT may be in part a reflection of earthworm activity as influenced by tillage. For example, earthworm midden counts were higher in NT compared to CT after long-term management at Ridgetown (Van Eerd et al, 2014) and elsewhere (Karlen et al, 1994), presumably because Table 3 Effect of crop rotation a on overall Cornell Soil Health Assessment (CSHA) and Ontario Soil Health Assessment (OSHA) score b in 0-15 cm depth from four long-term experiments.…”
Section: Tillage Systemmentioning
confidence: 99%
See 3 more Smart Citations